Plumbing engineering design handbook. Volume 3, a plumbing engineer's guide to system design and specifications (American Society of Plumbing Engineers, 2011)
This Handbook is designed to provide accurate and authoritative information for the design and specification of plumbing systems. This book has 12 chapters including such topics as fire protection systems, plumbing design for healthcare facilities, treatment of industrial waste, public swimming pools, gasoline and diesel oil systems, steam and condensate piping, solar energy, and more.